Identification and characterization of a rare fungus, quambalana cyanescens, isolated from the peritoneal fluid of a patient after nocturnal intermittent peritoneal dialysis - Kuan, C.S.; Yew, S.M.; Toh, Y.F.; Chan, C.L.; Lim, S.K.; Lee, K.W.; Na, S.L.; Hoh, C.C.; Yee, W.Y.; Ng, K.P. (Public Library of Science, 2015)
Peritonitis is the leading complication of peritoneal dialysis, which is primarily caused by bacteria rather than fungi. Peritonitis is responsible for approximately 18% of the infection-related mortality in peritoneal dialysis patients. In this paper, we report the isolation of a rare fungus, Quambalaria cyanescens, from the peritoneal fluid of a man after he switched from continuous ambulatory peritoneal dialysis to nocturnal intermittent peritoneal dialysis. Based on the morphological examination and multigene phylogeny, the clinical isolate was confirmed as Q. cyanescens. This pathogen exhibited low sensitivity to all tested echinocandins and 5-flucytosine. Interestingly, morphological characterization revealed that Q. cyanescens UM 1095 produced different pigments at low temperatures (25 degrees C and 30 degrees C) on various culture media. It is important to monitor the emergence of this rare fungus as a potential human pathogen in the tropics. This study provides insight into Q. cyanescens UM 1095 phenotype profiles using a Biolog phenotypic microarray (PM). Of the 760 nutrient sources tested, Q. cyanescens UM 1095 utilized 42 compounds, and the fungus can adapt to a broad range of osmotic and acidic environments. To our knowledge, this is the first report of the isolation of Q. cyanescens from peritoneal fluid, revealing this rare fungus as a potential human pathogen that may be misidentified using conventional methods. The detailed morphological, molecular and phenotypic characterization of Q. cyanescens UM 1095 provides the basis for future studies on its biology, lifestyle, and potential pathogenicity.